(3GdeMce aj GNJUGQ GdeYdes - (3eMH GdOjf GHi MGeO eMeO Hf Ndjd GdbOSi GdTGaYjs; (3GHf ZfGe , EHQGgje Hf jMji Hf ZfGe GdMQGfj GdebOSj GdfejQj, CHh WGgQ,J (B779 (3g` s ((3eMeO Hf CMeO Gdefhai s)
(3ChdgG (B:s
(3HYO GdHSedI hPcQ GdeDda bO hbaJ Ydi cKjQ ef cJH GdJYHjQ ade CQ ai GdeNJUQGJ GdefKhQI efgG cJGHG GfaY hdG GNUQ hdG GLeY s
(3BNQgG (B:s
(3aCNQL YdGeI aCQg ef MH , aSCdg ef Gi MH CNQLJgG abGd(B: (3dG COQi s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B126s
Keywords: (3JYHjQ GdQDjGs